Genome-wide analysis of the zebrafish ETS family identifies three genes required for hemangioblast differentiation or angiogenesis. - Liu, F; Patient, R (2008)
ETS domain transcription factors have been linked to hematopoiesis, vasculogenesis, and angiogenesis. However, their biological functions and the mechanisms of action, remain incompletely understood. Here, we have performed a systematic analysis of zebrafish ETS domain genes and identified 31 in the genome. Detailed gene expression profiling revealed that 12 of them are expressed in blood and endothelial precursors during embryonic development. Combined with a phylogenetic tree assay, this suggests that some of the coexpressed genes may have redundant or additive functions in these cells. Loss-of-function analysis of 3 of them, erg, fli1, and etsrp, demonstrated that erg and fli1 act cooperatively and are required for angiogenesis possibly via direct regulation of an endothelial cell junction molecule, VE-cadherin, whereas etsrp is essential for primitive myeloid/endothelial progenitors (hemangioblasts) in zebrafish. Taken together, these results provide a global view of the ETS genes in the zebrafish genome during embryogenesis and provide new insights on the functions and biology of erg, fli1, and etsrp, which could be applicable to higher vertebrates, including mice and humans.